How Can Post-Secondary Institutions Support Transfer Students? Lessons from Ontario - LaCroix, Emerson; Aurini, Janice (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur, 2025)
Studies of student mobility find that some transfer students experience “transfer shock” when changing institutions. While Canadian studies have identified instances of low academic performance and delayed time to completion, these are observed at single points in time and often capture student outcomes at the endpoint of post-secondary credentials. Our research adds qualitative nuance to the concept of “transfer shock” throughout the transfer process. Using 107 longitudinal interviews, we follow students (n = 56) as they traverse a variety of transfer pathways between two colleges and three universities in Ontario. In doing so, we identify the challenges students experience during their first year after transferring, and the extent to which academic and social challenges persist over time. We discuss the implications of these findings for post-secondary professionals who support transfer in the sector, and provide recommendations for alleviating transfer shock.